Generation and characterization of three clones (NCCSi007A, NCCSi007B and NCCSi007C) of an integration free induced Pluripotent Stem Cell line from a patient with alcoholic liver cirrhosis of Indian ethnicity - Mohsina Khan; Arun Vaidyanath; Deepika Suresh; Bhumika Vaishnav; Arjun Lal Kakrani; Swapnil Patil; Anjali Shiras (Stem Cell Research, 2020)
Three induced pluripotent stem cells (iPSC) clones NCCSi007-A, NCCSi007-B and NCCSi007-C were generated from CD4+T cells of a 38 years old male patient suffering from liver cirrhosis- alcoholic and minimal hepatic encephalopathy of Indian origin. The CD4+T cells of the patient were reprogrammed using integration free, Sendai viral vector system. Each of the three iPSC clones showed high alkaline phosphatase (ALP) activity, expressed pluripotency markers OCT4, SOX2, NANOG, KLF4, SSEA-4, TRA-1–60, showed normal male karyotype (46, XY) and exhibited multi-lineage differentiation.